Clinical Manifestation of Acute, Subacute, and Chronic Low Back Pain in Different Age Groups: Low Back Pain in 35, 446 Patients. Issue 8 (23rd June 2018) - Hüllemann, Philipp; Keller, Thomas; Kabelitz, Maria; Gierthmühlen, Janne; Freynhagen, Rainer; Tölle, Thomas; Forstenpointner, Julia; Baron, Ralf
Abstract: Background: Low back pain (LBP) is a major healthcare problem causing tremendous economic costs. Methods: Clinical manifestation of LBP was characterized in 35, 446 patients. We focused on the comparison of the acute, subacute, and chronic LBP stage with regard to patients' ages, based on epidemiologic and clinical questionnaires (eg, painDETECT Questionnaire, Pain Disability Index), pain intensity, pain descriptors, and functional impairment. Results: We found that neuropathic components were most frequent in chronic LBP patients at the ages of 51 to 60 years. Elderly LBP patients showed a decrease in neuropathic and an increase in nociceptive pain. The most frequently reported pain descriptors were "pressure pain" and "pain attacks" through all stages of LBP, whereas "burning" and "prickling" were most frequent in the chronic stage. Patients after back surgery presented neuropathic pain symptoms most frequently and had the highest amount of pain medication intake. Conclusions: Burning and prickling were revealed as possible indicators for LBP chronicity. Combined with pain attacks and pressure pain, these 4 pain descriptors might be a promising adjunct to pain intensity in terms of outcome parameters for future LBP studies. The decrease of neuropathic pain syndromes in the elderly might be explained by degenerative processes. The presented work provides important insights on LBP management in the acute, subacute, and chronic stages.